Resource Dependence and Strategies of a Scholarly Journal’s Two-Sided Platform - Orekhova S.V. (Ural State University of Economics, 2018)
The paper delves into resource dependence of Russian scholarly journals’ strategies on stakeholders. We state that a business model of a scholarly journal is a two-sided platform of a specific type where the platform’s core is multi-leveled and the target efficiency of the research object is hardly associated with financial profit. The authors distinguish the factors that determine a journal’s dependence on stakeholders. Based on resource dependence theory and stakeholder theory we prove that stakeholders influence the strategic choice of a journal with respect to a number of characteristics that determine its target efficiency. The study shows that the key stakeholder of a scientific journal is its owner. We identify the major response strategies of a scholarly journal to stakeholders’ requirements according to the resources available and discuss reasons behind a decrease in the level of target efficiency of Russian scientific journals. The obtained results can be of use for scientists and practitioners working in the market for scientific publications.